EFFECTS OF EARTH PRESSURE BALANCE SHIELD TUNNELLING ON GROUND SETTLEMENT - CHEE, KHOO MIN (2020)
Construction of tunnel results in ground movements with a settlement trough is well described by a Gaussian distribution curve. For near-surface settlements, it was established that the trough width i is an approximately linear function of the tunnel depth zo in relation to a trough width parameter K and broadly independent of tunnel construction method and tunnel diameter. The choice of an appropriate value of K may require some judgement, since it depends on whether the ground is primarily cohesive or frictional. Published literature recommended that for practical purposes K could be taken as 0.5 for tunnels in clays and 0.25 for tunnels in sands and gravels. The main aim of this research is to investigate the ground settlement induced by Earth Pressure Balance (EPB) shield tunnelling in local geology.